AMETIS Preplanned Ancillary Study: Impact of Agitation During Mechanical Thrombectomy Under Sedation - Tabillon, Caroline; Bernard, Rémy; Jacquens, Alice; Pommier, Maxime; Begard, Marc; Balança, Baptiste; Rapido, Francesca; Tavernier, Benoit; Molliex, Serge; Velly, Lionel; Verdonk, Franck; Lukaszewicz, Anne-Claire; et al. (Stroke (1970), 2025)
BACKGROUND: Mechanical thrombectomy is the treatment of choice for ischemic strokes of the anterior circulation with proximal occlusion. Mechanical thrombectomy can be performed under sedation, which can lead to episodes of periprocedural agitation. The aim of this study is to describe the prevalence of agitation and determine the consequences during and after mechanical thrombectomy. METHODS: This is an ancillary study to the AMETIS study (Anesthesia Management in Endovascular Therapy for Ischemic Stroke). We evaluated the patients from the sedation group of this randomized trial; some patients presented at least 1 episode of agitation during the procedure (determined by a Richmond Agitation-Sedation Scale score >1) prospectively collected. We explored the association between agitation and a composite outcome (Thrombolysis in Cerebral Infarction score <2b and/or arterial perforation) through univariate and multivariate analyses, accounting for confounders (agitation, age, National Institutes of Health Stroke Scale score, local thrombus) identified a priori by the acyclic diagram method. RESULTS: Among the 138 participants (average age, 71±14 years; 72 [52%] male; average National Institutes of Health Stroke Scale score, 15±6), 53 (38%) experienced at least 1 agitation episode. Agitation was neither a risk factor of Thrombolysis in Cerebral Infarction score <2b and/or arterial perforation in univariate and multivariate analyses (adjusted odds ratio, 1.29 [0.57-2.92]; P=0.5), nor a risk of unfavorable outcome (adjusted OR, 0.7 [0.18-2.56]; P=0.56). Although, agitated patients had a higher incidence of conversion with intubation (21% versus 5%; OR, 5.3 [1.7-20]; P<0.01) and significantly worse radiological image quality (62% versus 17%; OR, 8.37 [3.9-19.1]; P<0.01). CONCLUSIONS: Our study found a high frequency of agitation during mechanical thrombectomy under sedation. Despite the absence of any significant link with prognosis, Thrombolysis in Cerebral Infarction score, and perforations, there is more conversion to general anesthesia with intubation and poorer quality images.